Efficacy of a remote based computerised visual acuity measurement. Issue 7 (26th April 2012) - Srinivasan, Krithica; Ramesh, S Ve; Babu, Noushad; Sanker, Nijil; Ray, Avik; Karuna, S M
Abstract : Aim: To determine the efficacy of a remotely operated computer-based logarithmic (logMAR) visual acuity chart. Methods: Visual acuity was tested using a laptop or computer-based logMAR chart (COMPlog) for all subjects by two different methods. The methods differed by the physical presence and absence (remote) of an optometrist and in the mode of instructions provided. Remote access was obtained through the internet, using Teamviewer software to control the system linked to COMPlog and instructions were provided by telephone. The order of measurements and the eye to be tested was randomised. logMAR visual acuity and time taken were recorded. A questionnaire was used to assess the participant's feedback. Results: Intraclass correlation for visual acuity between the two methods (α=0.964, 95% CI 0.937 to 0.979). There was no statistically significant difference (p=0.648) in the median visual acuity measurement between the two methods (median difference 0.00, IQR 0.20 logMAR). The time taken between the two methods was not statistically significant (p=0.457). There was no significant difference in the responses to the questionnaire between the study methods (p=0.119). Conclusions: Tele (remotely controlled) visual acuity measurement is as reliable as that measured with the physical presence of an optometrist.